2020
DOI: 10.1111/bjh.16939
|View full text |Cite
|
Sign up to set email alerts
|

Progress in treating chronic granulomatous disease

Abstract: Chronic granulomatous disease is a primary immunodeficiency due to a defect in one of six subunits that make up the nicotinamide adenine dinucleotide phosphate oxidase complex. The most commonly defective protein, gp91 phox , is inherited in an X-linked fashion; other defects have autosomal recessive inheritance. Bacterial and fungal infections are common presentations, although inflammatory complications are increasingly recognized as a significant cause of morbidity and are challenging to treat. Haematopoiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 105 publications
0
24
0
8
Order By: Relevance
“…The incidence of inflammatory complications in patients with XLR-CGD is twice as high as that in patients with AR-CGD [6,18]. Appropriate anti-inflammatory agents, mainly corticosteroids, can significantly improve the prognosis of patients with CGD, and do not appear to increase the bacterial infection risk [3]. The recommended initial dose of prednisone is 1 mg/ kg daily and to be given for an average of 2-3 weeks before being tapered over several months [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of inflammatory complications in patients with XLR-CGD is twice as high as that in patients with AR-CGD [6,18]. Appropriate anti-inflammatory agents, mainly corticosteroids, can significantly improve the prognosis of patients with CGD, and do not appear to increase the bacterial infection risk [3]. The recommended initial dose of prednisone is 1 mg/ kg daily and to be given for an average of 2-3 weeks before being tapered over several months [19].…”
Section: Discussionmentioning
confidence: 99%
“…Defects in genes encoding various components of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase complex are associated with a dysfunctional respiratory burst, which decreases the ability of phagocytes to kill catalase-positive bacteria and fungi [2]. Mutations in CYBB, CYBA, NCF1, NCF2, NCF4, and CYBC1 genes have been associated with CGD [3]. About 70% of CGD cases are caused by defects in the CYBB gene, which is located on the short arm of the X chromosome (Xp21.…”
Section: Introductionmentioning
confidence: 99%
“…The cost-benefit balance for the therapeutic use of IFN-γ is favorable, especially for patients with the X-linked variant and with a history of invasive aspergillosis. Despite the benefits, IFN-γ drug therapy does not prevent granuloma formation and does not appear to improve symptoms of chronic inflammation [ 139 ]. On the other hand, working with cells from CGD patients and murine models, it has been shown that the blockade of the IL-1β receptor restores autophagy and inhibits the activity of the inflammasome, generating beneficial effects such as the attenuation of inflammation, resistance to invasive aspergillosis, and improvement of symptoms typical of colitis [ 140 ].…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
“…Rapamycin, an mTOR inhibitor and autophagy restorer, is capable of reducing the release of pro-inflammatory cytokines. Thus, it has been suggested that combination therapy with Anakinra and Rapamycin can be used to treat the inflammatory complications present in CGD patients [ 139 ].…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
“…The variation in outcomes might be attributable to different pioglitazone dosage, or to the often required combination therapy with antibiotics and/or interferon IFN-g. Further studies are necessary to determine if pioglitazone will provide a therapeutic option for CGD patients, for example as adjuvant therapy in severe bacterial infections or as prophylaxis. At this point only hematopoietic stem cell transplantation, gene therapy or gene editing with CRISPR-Cas9 offer a cure for CGD (272).…”
Section: Generation Of Compensatory Rosmentioning
confidence: 99%